Business Development Strategy of KALN: A Community-Based Men’s Activewear Brand in Indonesia - Almira, Lila; Saefudin, Nugraha (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to analyze the feasibility and business development strategy of KALN, a local men's fashion brand targeting automotive communities in Indonesia. The research adopts the Customer Value Theory, Design Thinking, Business Model Canvas (BMC), and the Timmons Model. A qualitative descriptive approach is employed through literature review, field observation, and interviews with automotive community members. The findings reveal that KALN holds strong market potential, particularly through the integration of functional, emotional, and social values in its product design. SWOT and BMC analyses indicate that KALN can compete by leveraging a community-based differentiation strategy. This article recommends digital marketing strategies, collaborations with communities, and enhanced brand engagement to support business growth.